Dynamic principal modeling of cemented phosphogypsum stabilized soil under dry and wet cycles - Zhangrong Ji; Kaisheng Chen; Kai Zhang (PLoS ONE, 2025)
Aiming at the influence of dynamic loading and wet/dry cycles during the operation of roadbed and in response to the proposal of Guizhou Provincial Government to promote the efficient utilization of phosphogypsum to solve the current situation of oversupply of phosphogypsum, the dynamic triaxial experiment was carried out to explore the dynamic constitutive model of phosphogypsum-stabilized soil with different numbers of wet/dry cycles, different peripheral pressures, and different consolidation ratios. The test results show that: (1) the effect of wet and dry cycles has a greater impact on the dynamic constitutive model of the mix, Monismith exponential model is suitable for the dynamic stress-strain curves in the case of wet and dry cycling; (2) The dynamic shear modulus-dynamic shear strain constitutive model of phosphogypsum stabilized soil was established based on dynamic soil mechanics, and the fitted correlation coefficients were all higher than 0.85, and the maximum values of MAE and RMSE were 4.827 and 5.990, respectively; (3) The prediction of the dynamic resilience modulus of phosphogypsum stabilized soil can be fitted by Ni model and power exponential model; (4) By comparing the dynamic and static modulus of rebound, it is concluded that the value of dynamic modulus of rebound for phosphogypsum-stabilized soil under dry and wet cycles is 1.1–1.5 times of the static modulus of rebound, and the recommended value of dynamic modulus of rebound is 90–100 MPa.